Content Analyses of Scientific Articles from Issues Published in Sport Mont Journal in 2004 - Milena Mitrovic (Journal of Anthropology of Sport and Physical Education, 2018)
Sport Mont Journal (SMJ) is a print and electronic scientific journal aims to present easy access to the scientific knowledge for sport-conscious individuals using contemporary methods. SMJ publishes original scientific papers, review papers, editorials, short reports, peer review - fair review, as well as invited papers and award papers in the fields of Sports Science and Medicine. In this working paper, we will analyze the papers from the journals published in 2004. The newspaper was published in 2004 twice, in May and September. In May issue was published 55 articles, and 24 in September. All papers were classified according to the science fields: sports training and training methodology, anthropology, sports history, research methodology, sports pedagogy, sociopsychology of sports, sports management, biomechanics, physiology and other works. A significant number of monographs have also been published in this publication.